Sulforaphane inhibits the growth of prostate cancer by regulating the microRNA-3919/DJ-1 axis - Zhang, Fangxi; Wan, Xiaofeng; Zhan, Jianmin; Shen, Ming; Li, Runsheng (Frontiers in Oncology, 2024)
Prostate cancer (PCa) is the second most common solid cancer among men in the world and is also the fifth leading cause of cancer deaths in men. Sulforaphane (SFN), a kind of isothiocyanate compound, has been shown to exert inhibition effects on a variety of tumor cancers. However, the biological functions of SFN in PCa has not been fully elucidated. The objective of the research was conducted to further investigate the possible underlying mechanism of SFN on PCa using in vitro cell culture and in vivo tumor model experiments. In the present study, SFN downregulated the mRNA and protein expression of DJ-1, an oncogenic gene. Small RNA sequencing analysis and dual-luciferase reporter assay confirmed that microRNA (miR)-3919 directly targeted DJ-1 to inhibition its expression. Furthermore, miR-3919 overexpression impeded viability, migration, invasion and promoted apoptosis of PCa cells. The tumor growth in nude mouse was also inhibited by miR-3919 overexpression and miR-3919 expression in PCa tissues was lower compared to peritumoral tissues by in situ hybridization assay. In addition, transfection of miR-3919 inhibitors partially reversed the effects of SFN on cell viability, migration, invasion and apoptosis. Overall, miR-3919/DJ-1 axis may be involved in the effects of SFN on the malignant biological behaviors of PCa cells, which 2 / 22 might be a new therapeutic target in PCa.